Extended Amygdala Neuropeptide Circuitry of Emotional Arousal: Waking Up on the Wrong Side of the Bed Nuclei of Stria Terminalis - Giardino, William J.; Pomrenze, Matthew B. (Frontiers in Behavioral Neuroscience, 2021)
Sleep is fundamental to life, and poor sleep quality is linked to suboptimal function of the neural circuits that process and respond to emotional stimuli. Wakefulness (“arousal”) is chiefly regulated by circadian and homeostatic forces, but affective mood states also strongly impact the balance between sleep and wake. Considering the bidirectional relationships between sleep/wake changes and emotional dynamics, we use the term “emotional arousal” as a representative characteristic of the profound overlap between brain pathways that 1) modulate wakefulness, 2) interpret emotional information, and 3) calibrate motivated behaviors. Interestingly, many emotional arousal circuits communicate using specialized signaling molecules called neuropeptides to broadly modify neural network activities. One major neuropeptide-enriched brain region that is critical for emotional processing and has been recently implicated in sleep regulation is the bed nuclei of stria terminalis (BNST), a core component of the extended amygdala (an anatomical term that also includes the central and medial amygdalae, nucleus accumbens shell, and transition zones betwixt). The BNST encompasses an astonishing diversity of cell types that differ across many features including spatial organization, molecular signature, biological sex & hormonal milieu, synaptic input, axonal output, neurophysiological communication mode, and functional role. Given this tremendous complexity, comprehensive elucidation of the BNST neuropeptide circuit mechanisms underlying emotional arousal presents an ambitious set of challenges. In this review, we describe how rigorous investigation of these unresolved questions may reveal key insights to enhancing psychiatric treatments and global psychological wellbeing.